Плащом и кинжалом: [роман] / Антон Ильин - Ильин Антон (Приказано выжить, 2002)
Экземпляры: ф.11 (2003) / Инвентарный номер: 47385 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: И 46 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44